Beyond The Clinic: an Investigation of Antibiotic Resistance Awareness Among Public - Mokashi, Pratiksha; Dedge, Sakshi; Sakure, Sunita (Journal of Neonatal Surgery, 2025)
Antibiotics, Antibiotic resistance, Antimicrobial resistance, Multidrug resistance, Stewardship. Antibiotic resistance is occurring everywhere in the world, compromising the treatment of infectious diseases and undermining many other advances in health and medicine. It represents one of the biggest threats to global health today, and can affect any one, of any age, in any country. It leads to longer hospital stays, higher medical costs and increased mortality. Antibiotic resistance occurs naturally, but misuse of antibiotics in humans and animals is accelerating the process. Tackling antibiotic resistance is a high priority for the World Health Organization (WHO). WHO is coordinating a global campaign to raise awareness and encourage best practices among the public, policymakers, health and agriculture professionals. This survey provides a snapshot of current public awareness and common behavior related to antibiotics in a range of countries. Our objectives include creating awareness among people about the antibiotic resistance, to analyze the problem of antibiotic resistance by conducting a survey among people and to find the possible solutions to overcome the problem of antibiotic resistance. This survey will provide an insight into the level of AMR awareness and antibiotic use in public. Through the response of 200 individuals, we can say that there is an overall poor understanding of antimicrobial resistance and/or improper use of antibiotics among the people